Organisational behaviour associated with emotional contagion among direct selling members - Hashim, Junaidah; Wok, Saodah; Ghazali, Ruziah (Emerald Group Publishing, 2008)
Purpose – This paper aims to examine organisational behaviour as a result of emotional contagion experienced by selected members in direct selling companies. Specifically, it seeks to investigate how members in a group are affected by the happiness of their high achievers, what factors influence the emotional contagion to occur, and what are the effects of emotional contagion on individual, group and organisation work outcomes. Design/methodology/approach – The variables studied were emotional contagion, personal characteristics, group outcomes and organisational outcomes. Emotional contagion was measured by self-report of impulsive acts; while personal characteristics were measured in terms of social desirability, extraversion, locus of control, live accomplishment, materialistic world, susceptibility to interpersonal influence, and self-esteem. Organisational outcome variables were measured in terms of organisational commitment and organisational culture. Other variables studied were group behaviour, team player, demographic characteristics, and business organisational characteristics. A total of 276 respondents participated in this study. Findings – It is found that emotional contagion is positively related with personal outcomes. Further findings reveal that emotional contagion has an impact on both the group and the team. The team, as a whole, is influenced not only by the emotional contagion but also by the personal characteristics of the respondents. Emotional contagion is also related to organisational outcomes. Both the group characteristics are positively related with organisational commitment. Emotional contagion is also positively related to organisational culture. Group characteristics are also positively related with organisational culture. It can be postulated that the following relationships exist between emotional contagion, personal outcomes, group outcomes, and organisational outcomes. It is also found that emotional contagion is a very important variable in the light of personal characteristics, group characteristics and organisational characteristics. Originality/value – The paper focuses on a specific industry in Malaysia – direct selling – where no such study has been conducted in the past.